(untitled) (Experimental biology, 2015)
Gagea pusilla is spring geophyt, characterized by mixed reproductive strategies. They relies on vegetative reproduction by subterranean bulbils in young stages but completely switches to sexual reproduction once a certain bulb size is attained. In this study AFLP-genotyping method was used to investigate the consequences of these reproductive strategies for genetic diversity. In most cases G. pusilla has generative reproduction and it is reflected by the comparatively high genotypic richness within populations and the low numbers of samples per clone.